Survival outcomes for stage‐matched endoscopic and open resection of olfactory neuroblastoma. Issue 12 (25th September 2017) - Harvey, Richard J.; Nalavenkata, Sunny; Sacks, Raymond; Adappa, Nithin D.; Palmer, James N.; Purkey, Michael T.; Schlosser, Rodney J.; Snyderman, Carl; Wang, Eric W.; Woodworth, Bradford A.; Smee, Robert; Havas, Tom; et al.
Abstract: Background: Advanced‐stage olfactory neuroblastoma requires multimodal therapy for optimal outcomes. Debate exists over endoscopic endonasal surgery in this situation. Stage‐matched open and endoscopic surgical therapy were compared. Methods: Patients from 6 cancer institutions were assessed. Stratification included dural involvement, Kadish stage, nodal disease, Hyams' grade, approach, and margin status. At follow‐up, local control, nodal status, and evidence of distant metastases were recorded with any subsequent therapy. Statistical analyses to identify risk factors for developing recurrence and survival differences were performed. Results: One hundred nine patients were assessed (age 49.2 ± 13.0 years; 46% women) representing Kadish A stage (10%), Kadish B stage (25%), and Kadish C stage (65%). The majority of the patients (61.5%) underwent endoscopic resection, 53.5% within Kadish C stage. Within‐stage survival analysis favored endoscopic subgroup for Kadish C stage (log‐rank P = .017) nonsignificant for Kadish B stage (log‐rank P = .39). Conclusion: Stage‐matched survival was better for the endoscopically treated group compared to the open surgery group, with high negative margin resections obtained.